Prosecuting serious human rights violations - Seibert-Fohr, Anja (Oxford University Press, 2009)
Is there a duty to prosecute serious human rights violations? This text examines this issue, drawing on international human rights instruments and case law. It finds flaws in the prosecution of these crimes and develops proposals for improvement.